Enhancing quality across industries: A systematic literature review on the impact of six sigma - Ahmad Syamil; Mohammad Ichsan; Muhammad Syahrazly; Maharani Putri Fadjar; Irza Raihan Revidia (Global Business & Finance Review (GBFR), 2023)
Purpose: The objective of this study is to conduct a systematic literature review on the impact of Six Sigma in various industries. Design/methodology/approach: A total of 83 articles from respected international journals published between 2015 and 2020 were selected and analyzed. The inclusion criteria ensured that the articles focused on quality improvement using the Six Sigma approach and were published by reputable publishers. Findings: The f indings of the s tudy reveal that manufacturing emerged as the most prevalent sector, with 17 studies dedicated to it. Among the selected articles, case studies were the most employed research method, accounting for 59 studies. Moreover, the study highlights the primary benefits associated with implementing Six Sigma. The most notable benefit is the reduction of defect rates, followed by improvements in efficiency and cost reduction. the primary benefit of Six Sigma is the reduction of defects (52 cases or 42.75%), followed by improvement in efficiency (49 cases or 37.40%), and then cost reduction (26 cases or 19.85%). Research limitations/implications: Based on the results, the study recommends that organizations adopt Six Sigma to enhance the quality of their processes, increase efficiency, and minimize costs. Originality/value: T his recommendation is p articularly relevant f or t he m anufacturing s ector, which s howcased the highest concentration of research studies in the literature.
Keywords: 650; Six Sigma; Lean Six Sigma; Operations Management; Lean Manufacturing; Systematic Literature Review (SLR); Total Quality Management (TQM); Quality Improvement